2016
DOI: 10.3390/f7110280
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics and Water-Use Efficiency of Siberian Elm Trees (Ulmus pumila L.) within Arid Regions of Northeast Asia

Abstract: Abstract:The Siberian elm (Ulmus pumila L.) is one of the most commonly found tree species in arid areas of northeast Asia. To understand the morphological and physiological characteristics of Siberian elms in arid regions, we analyzed leaves from seven study sites (five arid or semi-arid and two mesic) in China, Mongolia and the Republic of Korea, which covered a wide range of average annual precipitation (232 mm·year −1 to 1304 mm·year −1 ) under various aridity indexes (AI) and four different microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 85 publications
2
15
0
Order By: Relevance
“…Ulmus pumila is one of the most xerophytic elm species [18,56], and its strategy of acclimation in moisture-limited regions is based on several anatomical features and physiological mechanisms. Despite the very large vessels that are potentially more vulnerable to cavitation, elm has an effective phenotypic regulation of transpiration at the level of stomatal morphology [57]. As in a typical ring-porous tree, the sap flows mainly through the earlywood vessels of the last ring, and the contribution of the preceding rings does not exceed 10% [58,59], primarily because of losing the hydraulic conductivity of very large earlywood vessels in winter [60].…”
Section: Climatic Response and Growth Modeling Of Treesmentioning
confidence: 99%
“…Ulmus pumila is one of the most xerophytic elm species [18,56], and its strategy of acclimation in moisture-limited regions is based on several anatomical features and physiological mechanisms. Despite the very large vessels that are potentially more vulnerable to cavitation, elm has an effective phenotypic regulation of transpiration at the level of stomatal morphology [57]. As in a typical ring-porous tree, the sap flows mainly through the earlywood vessels of the last ring, and the contribution of the preceding rings does not exceed 10% [58,59], primarily because of losing the hydraulic conductivity of very large earlywood vessels in winter [60].…”
Section: Climatic Response and Growth Modeling Of Treesmentioning
confidence: 99%
“…Appropriate species selection and soil treatments in reforestation activities facilitate the restoration of land, as shown by Ganchudur (2019) in Bulgan province. Park et al (2016) found that indigenous Siberian elm trees (Ulmus pumila) growing in arid areas are able to substantially alter their morphological and physiological characteristics to avoid heat stress and increase water conservation. Tree height, leaf size, and stomatal area per unit area decreased with increasing site aridity, while leaf mass per unit leaf area and water-use efficiency increased.…”
Section: Afforestation Initiativesmentioning
confidence: 99%
“…This phenomenon was observed in the Taklamakan desert dunes, where the growth of trees has decreased as the dunes have become taller [20]. Plants are known to show improved water use efficiency under drought conditions [21][22][23]. One major change seen during drought stress is a reduction in plant height, which decreases the water transport distance from root to leaf [24][25][26].…”
Section: Introductionmentioning
confidence: 97%